Morphological and chemical characteristics of black gram (Vigna mungo L.) sprouts produced in a modified atmosphere chamber at four seeding densities - Choon, Sea Yeat; Ahmad, Siti Hajar; Ding, Phebe; Sinniah, Uma Rani; Abdul Hamid, Azizah (Universiti Putra Malaysia Press, 2010)
A modified atmosphere with low oxygen and high carbon dioxide sprouting environments can be used to regulate sprout growth. By monitoring seeding density used for sprouting, stress ethylene is produced due to the compactness within sprouting pot. A study on the morphological and chemical characteristics and the total phenolic compounds of black gram sprouts (Vigna mungo), grown in a hermetically sealed chamber, was conducted using four seeding densities (50, 75, 100, and 125 g seeds L-1). For this purpose, the selected presoaked seeds were put into a pot and placed in the chamber. The seeds were allowed to sprout for four days and watering was done every three hours for 20 minutes. Sprouts produced with lower seeding density (50 and 75 g seeds L-1) were long and etiolated with long roots and higher sprout weight. In higher seeding density (100 and 125 g seeds L-1), on the contrary, sprout length was shorter with short roots and lower sprout weight, and the ratio between hypocotyl and root length was 1:1. Meanwhile, there were no significant differences in hypocotyl diameter of sprouts produced. Sprouts produced at a lower seeding density had 2.7% lower soluble solids concentration, but they had 18% higher contents of ascorbic acid as compared to the ones produced in higher seeding density. Similarly, there were significant differences in the total phenolic compounds of sprouts and the contents decreased by 43% as the seeding densities increased. Over-crowding and lack of watering produced poor quality sprouts. Thus, seeding density and watering duration during sprouting in a hermetically sealed chamber need to be determined for sustainable sprout production, as well as to produce safe sprouts as demanded by consumers.